2012
DOI: 10.1590/s0100-06832012000500022
|View full text |Cite
|
Sign up to set email alerts
|

Carbon balance and crop residue management in dynamic equilibrium under a no-till system in Campos Gerais

Abstract: SUMMARYThe adoption of no-tillage systems (NT) and the maintenance of crop residues on the soil surface result in the long-term increase of carbon (C) in the system, promoting C sequestration and reducing C-CO 2 emissions to the atmosphere. The purpose of this study was to evaluate the C sequestration rate and the minimum amount of crop residues required to maintain the dynamic C equilibrium (dC/ dt = 0) of two soils (Typic Hapludox) with different textural classes. The experiment was arranged in a 2 x 2 x 2 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
5
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 16 publications
5
5
0
1
Order By: Relevance
“…Recently, Ferreira et al . () reported that for this region, the minimum amount of biomass‐C input to maintain the steady state was 3·21 Mg ha −1 y −1 , and in this study, the biomass‐C input was 4·15 Mg ha −1 y −1 . The percentage of biomass‐C converted into SOC in this study was 14·2 and was very similar with the findings obtained by Ferreira et al .…”
Section: Resultssupporting
confidence: 49%
See 3 more Smart Citations
“…Recently, Ferreira et al . () reported that for this region, the minimum amount of biomass‐C input to maintain the steady state was 3·21 Mg ha −1 y −1 , and in this study, the biomass‐C input was 4·15 Mg ha −1 y −1 . The percentage of biomass‐C converted into SOC in this study was 14·2 and was very similar with the findings obtained by Ferreira et al .…”
Section: Resultssupporting
confidence: 49%
“…The main reason was the low amount of biomass-C added through residues of summer crop and winter species during the 29 years of experiment and the near absence of legumes as a winter cover crop (Table II). Recently, Ferreira et al (2012) reported that for this region, the minimum amount of biomass-C input to maintain the steady state was 3Á21 Mg ha À1 y À1 , and in this study, the biomass-C input was 4Á15 Mg ha À1 y À1 . The percentage of biomass-C converted into SOC in this study was 14Á2 and was very similar with the findings obtained by Ferreira et al (2012), which was~12Á63-14Á26%.…”
Section: Depletion Of Soil Organic Carbon and Total Nitrogen Upon Consupporting
confidence: 52%
See 2 more Smart Citations
“…However, it is crucial to identify the different fractions, as well as the forms of protection under natural vegetation and various agro-management systems (FIGUEIREDO et al, 2010).…”
Section: Introductionmentioning
confidence: 99%